Peningkatan Kemampuan Artikulasi Bernyanyi Menggunakan Metode Demonstrasi Pada Anak Tunagrahita Sedang di SLB Paulus Tomohon - Manusu, Lina T.; Siwi, Femmy D.; Marentek, L.K.M; Kiriweno, Henny B.A (Peneliti.net, 2026)
This study aims to determine the improvement in singing articulation skills in children with moderate intellectual disabilities at SLB Paulus Tomohon through the application of the demonstration method. This study uses a quantitative approach with a single subject experimental research design (Single Subject Research) A-B-A design. The research subject was a student with moderate intellectual disabilities in grade II of SLB Paulus Tomohon. Data were collected through observation, interviews, and performance tests measured in three conditions: baseline 1 (A1), intervention (B), and baseline 2 (A2). The results showed an improvement in singing articulation skills after the application of the demonstration method. The mean level score increased from 2.2 (A1) to 8 (B) and 11 (A2), with trend stability increasing from 40% to 100%. Thus, the demonstration method is effective in improving singing articulation skills in children with moderate intellectual disabilities and maintaining learning outcomes after the intervention is stopped.